2021
DOI: 10.1590/s1678-9946202163001
|View full text |Cite
|
Sign up to set email alerts
|

High molecular prevalence of HPV and other sexually transmitted infections in a population of asymptomatic women who work or study at a Brazilian university

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 30 publications
(49 reference statements)
1
22
0
1
Order By: Relevance
“…This scenario is not restricted to the Amazon region, given that similar sexual behavior has been observed in university students from other regions of Brazil [31,52] and from other countries, around the world [53][54][55]. Even so, as high rates of sexual infection by C. trachomatis are typical of the young populations of remote Amazonian communities [28,34], it would seem reasonable to assume that the ndings of the present study represent only the "tip of the iceberg" of the real epidemiological scenario of the infection in this region.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This scenario is not restricted to the Amazon region, given that similar sexual behavior has been observed in university students from other regions of Brazil [31,52] and from other countries, around the world [53][54][55]. Even so, as high rates of sexual infection by C. trachomatis are typical of the young populations of remote Amazonian communities [28,34], it would seem reasonable to assume that the ndings of the present study represent only the "tip of the iceberg" of the real epidemiological scenario of the infection in this region.…”
Section: Discussionmentioning
confidence: 73%
“…In Brazil, the absence of a monitoring program contributes to the unawareness of this silent epidemic and its recurrent damages, however, the annual number of hospitalizations of women with PID is over 45,000 [22]. The studies have reported prevalence of 4-20.5% in both asymptomatic women [23][24][25][26][27][28][29][30][31] and those seeking gynecological treatment [32][33][34]. The few available studies about genotyping for Brazil have recorded predominant frequencies of genotypes D, E and F of C. trachomatis, however, this is insu cient to understand what this infection behaves like in Brazil [28,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adicionalmente, estudios de otros países en población general han reportado prevalencias más bajas. Así, en Guinea Bissau, en 500 personas con edades entre 16 y 49 años, fue del 0,8 % [20]; en 210 mujeres de una universidad de Brasil, del 1,9 % [21], y en 2608 sujetos de una zona rural del suroeste China, fue del 1,2 % [22].…”
Section: Discussionunclassified
“…According to the results of this study, BV was found to be related to HPV-51, -52 infections. Previews study in Africa suggested that BV associate with HPV-58 [ 24 ]. Obviously, the epidemiology of HPV and genital tract infection is different in each region, and the founding of this study may guide the HPV vaccine protecting patients with recurrent BV.…”
Section: Discussionmentioning
confidence: 99%